The Growth of Species and the Making of Timeless Forms: Divine Objects and Extraordinary Bodies in Fijian Ritual Polities. Issue 1 (11th March 2018) - Abramson, Allen
Abstract : Oceanic polities and social organizations are often characterized as life‐giving systems that reproduce specific modes of humanity in ritual cycles of cosmogony or in regenerative flows of ancestral substance and relatedness. These portrayals typically enforce a strong ontological contrast between the properties of human beings and those of their immortal forebears. This paper shows in detail how, far from reproducing human life as a dilution of ancestral timelessness in a specifically human realm, Fijian ritual polities act as 'paradise machines', working to assemble precisely configured axes of natural species, human beings, manufactured objects, ancestors, and divinities as simulacra of the mythically narrated and danced domain of Nakauvadra. By comprehending Fijian ritual polities as hopeful denials of specifically human being, light is shed upon the cosmological significance of familiar modes of ritual hierarchy and ceremonial gift‐giving, but also of technical synthesis that has as its mission the material recomposition of these axes of timeless forms and relations: or, as in the case of sorcery, their deathly technical negation.